A review of volatiles in the Martian interior. (6th October 2016) - Filiberto, Justin; Baratoux, David; Beaty, David; Breuer, Doris; Farcy, Benjamin J.; Grott, Matthias; Jones, John H.; Kiefer, Walter S.; Mane, Prajkta; McCubbin, Francis M.; Schwenzer, Susanne P.
Abstract: Multiple observations from missions to Mars have revealed compelling evidence for a volatile‐rich Martian crust. A leading theory contends that eruption of basaltic magmas was the ultimate mechanism of transfer of volatiles from the mantle toward the surface after an initial outgassing related to the crystallization of a magma ocean. However, the concentrations of volatile species in ascending magmas and in their mantle source regions are highly uncertain. This work and this special issue of Meteoritics & Planetary Science summarize the key findings of the workshop on Volatiles in the Martian Interior (Nov. 3–4, 2014), the primary open questions related to volatiles in Martian magmas and their source regions, and the suggestions of the community at the workshop to address these open questions.